A small heat shock protein important in plant defense is targeted by the Xanthomonas axonopodis pv. manihotis HpaF Effector (2017)
Xanthomonas axonopochs pv. manihotis (Xam) is the causal agent of bacterial blight in cassava (Manihot esculenta) and, like many plant pathogens, relies on the secretion of type three effectors (T3E) to disrupt plant defense and favor disease development. HpaF is a core T3E conserved among several Xam strains from diverse origins and has a role as suppressor of plant defenses elicited by Pattern Triggered Immunity (PTI). A cassava protein that interacts with HpaF was previously identified in our laboratory using a yeast-two-hybrid screen against a cassava cDNA library. This interactor was named HpaF Interactor 1 (HF11) and corresponds to an HSP20-like chaperone. This protein was thought to be important in A. thaliana plant defense, as a mutant line for the HF11 gene ortholog has PTI impairments. However, the same could not be concluded for the protein in cassava due to the complexity in the generation of mutants for this plant. Here we confirmed and validated the interaction between HpaF and HF11 using protein co-immunoprecipitation. We also showed that the HF11 mutant from A. thaliana is complemented when transformed with HF11 from cassava, confirming the functional homology of these proteins. This is the first approach towards the characterization of a cassava protein interacting with a Xam T3E.